A Brazilian perspective of power systems integration using OSeMOSYS SAMBA – South America Model Base – and the bargaining power of neighbouring countries: A cooperative games approach. (April 2018) - de Moura, Gustavo Nikolaus Pinto; Legey, Luiz Fernando Loureiro; Howells, Mark
Abstract: This paper intends to contribute to a better understanding of both advantages and drawbacks of power systems interconnection processes between Brazil and its South American neighbours. Based on data available in national and international reports, three scenarios for the power supply sector expansion were modelled in OSeMOSYS. The Brazilian perspective of power integration considers funding strategic hydro projects in Argentina, Bolivia, Guyana and Peru. An alternative to the power integration process considers higher penetration of distributed photovoltaics and biogas power plants as well as lower hydro capacity expansion in Brazil. Features related to costs, carbon emissions, hydro reservoirs, technological performance, electricity demand, population growth, time zones and reserve margin were considered. The comparison of different scenarios provides insights regarding the contribution of renewable energy generation and sheds light on cross-border trade perspectives between Brazil and other countries in South America. Using a cooperative games approach, the bargaining power of each country (player) was calculated by applying the Shapley value concept. Argentina, Brazil, Paraguay, Peru and Guyana have the largest bargaining power, either as exporter or importer. Highlights: We model the long-term dynamics of power systems integration in South America. Two scenarios simulate the evolution of cross-border electricity trade. A cooperative game theory approach based on the Shapley value concept was used. Brazil, Peru, Paraguay, Guyana and Argentina have the largest bargaining power. The proposed methodology may support policy makers during international negotiations.